ETIKA BISNIS ISLAM DI KALANGAN PEDAGANG PASAR MANAQIB TQN SURYALAYA - Jamaludin Jamaludin; Dudang Gozali (Prodi Hukum Ekonomi Syariah (Muamalah), 2018)
Business ethics is a study of true or false moral. People doing business aims to findas much profit as possible, even using unethical means. The conventional classic economiclaw controls the capital as small as possible and dredge profits as good as possible. Thusmaking the business people to justify everything. It's no surprise that business people donot pay attention to social responsibility and business ethics. This research aims to knowthe Islamic business and to know the attitudes of the traders in the market Manaqibalready in accordance with Islamic business ethics. Research is done by collecting datafrom a variety of sources: books, magazines, journals or other writings and is supported by direct observation or observation and interviews and then then Symbolisions. The methodused in this research is a descriptive method with a normative juridical approach. Anormative juridical approach is an approach made based on key legal materials byexamining theories, concepts, principles of law and legislation. From the results of theresearch found that traders understand the ethical selling good by offering goods in anhonest, trustworthy, polite, and do not conceal the defective goods. When it is stored byother merchants they keep it well. Traders are traders who are ethics of Islamic business,because almost all traders in the market Manaqib have applied the foundations of Islamicbusiness ethics on the implementation of its businesses